Armstrong's handbook of human resource management practice - Armstrong, Michael, 1928-; Taylor, Stephen, 1965- (KoganPage, 2020)
"Armstrong's Handbook of Human Resource Management Practice is the bestselling and definitive resource for HRM students and professionals to understand and implement HR in relation to the needs of the business as a whole. It contains in-depth coverage of all the areas essential to the HR function such as employment law, employee relations, learning and development, performance and reward, as well as the HR skills needed to ensure professional success, including those related to leadership, managing conflict, interviewing and using statistics. In full-colour and with a range of pedagogical features to consolidate learning including source review boxes, key learning points summaries and case studies from international organizations such as IBM, HSBC and Oxfam, this fully updated fifteenth edition includes new chapters on the HRM role of line managers, evidence-based HRM, E-HRM and the gender pay gap as well as further case studies and updated wider content with the latest research and developments. Armstrong's Handbook of Human Resource Management Practice is aligned with the Chartered Institute of Personnel and Development (CIPD) profession map and standards and is ideally suited to both professionals and those studying HR qualifications, including undergraduate degrees and the CIPD's level 5 and 7 qualifications. Online supporting resources include comprehensive handbooks for lecturers and students, lecture slides, questionnaire, checklist toolkits, a literature review, glossary and bibliography"--
"First edition published in 1977 as A Handbook of Personnel Management Practice by Kogan Page"--Title page verso
Keywords: personální management; lidský kapitál; personnel management; human capital; učebnice vysokých škol; příručky; textbooks (higher); handbooks and manuals